Histone H1 chaperone activity of TAF‐I is regulated by its subtype‐dependent intramolecular interaction. (2nd March 2017) - Kajitani, Kaori; Kato, Kohsuke; Nagata, Kyosuke
Abstract : Linker histone H1 is involved in the regulation of gene activity through the maintenance of higher‐order chromatin structure. Previously, we have shown that template activating factor‐I (TAF‐I or protein SET) is involved in linker histone H1 dynamics as a histone H1 chaperone. In human and murine cells, two TAF‐I subtypes exist, namely TAF‐Iα and TAF‐Iβ. TAF‐I has a highly acidic amino acid cluster in its C‐terminal region and forms homo‐ or heterodimers through its dimerization domain. Both dimer formation and the C‐terminal region of TAF‐I are essential for the histone chaperone activity. TAF‐Iα exhibits less histone chaperone activity compared with TAF‐Iβ even though TAF‐Iα and β differ only in their N‐terminal regions. However, it is unclear how subtype‐specific TAF‐I activities are regulated. Here, we have shown that the N‐terminal region of TAF‐Iα autoinhibits its histone chaperone activity via intramolecular interaction with its C‐terminal region. When the interaction between the N‐ and C‐terminal regions of TAF‐Iα is disrupted, TAF‐Iα shows a histone chaperone activity similar to that of TAF‐Iβ. Taken together, these results provide mechanistic insights into the concept that fine tuning of TAF‐I histone H1 chaperone activity relies on the subtype compositions of the TAF‐I dimer. Abstract : A linker histone H1 chaperone TAF‐I consists of two subtypes, TAF‐Iα and TAF‐Iβ. TAF‐Iα exhibits less histone H1 chaperone activity compared with TAF‐Iβ even though TAF‐Iα and β differ only in their N‐terminal regions that are not essential for the chaperone activity. We found that the N‐terminal region of TAF‐Iα interacts with the acidic tail of its partnered TAF‐I monomer and inhibits the chaperone activity.